PEMBUATAN FRUITGHURT DARI KULIT PISANG KEPOK (Musa Paradisiaca L. var. Kepok) BERDASARKAN WAKTU FERMENTASI SEBAGAI RANCANGAN LEMBAR KERJA PESERTA DIDIK (LKPD) MATERI BIOTEKNOLOGI KONVENSIONAL DI SMA - Triana, Nita; ', Darmawati; Mahadi, Imam (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstract: The study was conducted to obtain the quality of banana peel kepok fruit gravy (Musa paradisiaca L. var Kepok.) Based on the right fermentation time (SNI 01-2981-1992) to be designed in Student Leaflet (LKPD) Conventional Biotechnological Material in high school. The study was conducted in April-May 2017. The research was carried out by two phases, namely the manufacture of leather goods fruitghurt kepok banana (Musa paradisiaca l. Var. Kepok) and LKPD design phase. This study was performed with fully randomized intentional (CRD) 5 treatments 3 replications, to obtain the number of samples. The measured parameters were levels of lactic acid, protein content, fat content, pH and organoleptic properties which included color, taste, odor, texture and preferred level panelists. The results showed that the fermentation time fruit hatch affects the quality of each treatment. When the A4 treatment fermentation time of 48 hours fruitgurt quality corresponding to (SNI 01-2981-1992) the lactic acid concentration of 0.79%, 3.60% protein, fat content 1.49% and a pH of 3.91. For descriptive Results with a texture of 4.70 (very strong), 4.80 color (dark brown), a sense of 4.50 (slightly acidic) and the aroma of 4.83 (very typical fruit gravy). The results of the research are used as Design Worksheet Students (LKPD) Biotechnology Conventional Materials at High School.Keywords: Fermentation Time, Fruit Grain, Worksheet Students (LKPD)